Local economic development, industrial policy and sustainable development in South Africa : a critical reflection on three new policy frameworks - Rivett-Carnac, Kate (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (School of Public Management and Planning))--Stellenbosch University, 2008.